The Effect of NaOH Concentration in The Pulping Process on Yield and Organoleptic of Art Paper from Citronella Distillation Waste - Helsa Marda S.R; Sri Mutiar; Anwar Kasim (Universitas Darussalam Gontor, 2023)
Many types of paper are on the market according to their intended use. Art paper is a type of paper with an attractive appearance, aesthetically rich in natural and unique nuances used by mostcraftsmen. Making art paper usually uses cellulose fiber that comes from trees, so it has an impact on deforestation. This research aims to use fragrant citronella waste as an alternative to trees as raw material for paper. Lemon grass and the availability of distillate waste which has a high enough cellulose content as a raw material for paper. The method in this study is the manufacture of pulp through the alkaline method. The analysis of organoleptic properties includes surface texture, appearance, color, and degree of whiteness. The treatment in making art paper is the difference in NaOH concentration of 5%, 7%, 9%, 11% and 13%. Analysis of organoleptic properties includes surface texture, appearance, colour, and degree of whiteness. The design used in this study was a completely randomised design with 3 replications. Data were analysed using ANOVA and Duncan's test at a significant level of 0.05.. The results showed that the yield of citronella distillation waste pulp ranged from 32.53 to 34.59%. The organoleptic properties of citronella waste art paper panelists' assessment of art paper products varied greatly. Brighter colors tend to be preferred over brownish colors, the rough texture and the appearance of visible fibers make art paper more attractive. The degree of whiteness of the resulting art paper ranges from 43.39 –48.95%